MONITORING TOOLS TO ASSESS VEGETATION SUCCESSIONAL REGRESSION AND PREDICT CATASTROPHIC SHIFTS AND DESERTIFICATION IN MEDITERRANEAN RANGELAND ECOSYSTEMS (Desertification in the Mediterranean Region a Security Issue)
The relationship between grazing intensity and ecosystem performance is complex and can depend on the prevailing ecological conditions. Previous studies have revealed that, in traditional grazing ecosystems, grazing can reduce ecosystem diversity in poor soils, but increase diversity and productivity in rich ecosystems subject to moderate grazing pressure. We are interested in detecting long-term structural changes or drift in an ecosystem before it is too late to prevent irreversible degradation. We analyzed vegetation spatial patterns and complexities of four Mediterranean communities: Tihmadit Region (Middle Atlas, Morocco), Camiyayla (Namrum) Region (Taurus Mountain, Turkey), Sykia Region (south of the Sithonia Peninsula, Greece), and Cabo de Gata Nijar Natural Park, Spain. Grazing disturbance was most intense near shelter and water points, which lead to gradients in soil surface disruption, compaction, and changes in the composition and cover of perennial vegetation. Dense matorral was more resistant to species loss than were moderately dense and scattered matorral, and grassland. Information fractal dimension decreased as we moved from a dense matorral to a discontinuous matorral, and increased as we moved to a more scattered matorral and to a grassland, which resulted in two opposing processes (interaction declining with ecosystem development, and immigration increasing with degradation) in a common pattern, i.e., small patches homogeneously distributed in the landscape. Characteristic species of the natural vegetation declined in frequency and organization in response to higher grazing disturbance, while species of disturbed areas exhibited the opposite trend. Overall, the spatial organization of the characteristic plants of each community decreased with increasing vegetation degradation, with the intensity of the trend being related to the species’ sensitivity to grazing. Developmental instability analyses of key species were used to determine the sensitivity of dominant key species to grazing pressure. Palatable species, which are better adapted to being eaten, such as Periploca laevigata, Phillyrea latifolia and Genista pseudopilosa, were able to resist moderate grazing pressure, while species of disturbed, grazed sites did not change developmental instability in response to increasing grazing pressure, such as Thymus hyemalis, Teucrium lusitanicum and Cistus monspeliensis. The usefulness of these monitoring tools in preventing land degradation is discussed.